Time-of-day-dependent effects of exercise on the hepatic clock and proteome in high-fat diet-fed mice - Chunxiu Huang; Xiaodan Wang; Huanghao Zhou; JingFang Zhu; Yue Hu; Huijuan Wu; Xinru Yu; Cong Chen (Journal of Physiology and Biochemistry, 2026)

N-doped hollow carbon nanocage-CNT confined FeNi nanoreactors for PMS activation toward sulfadiazine degradation - Junchang Wang; Yulai He; Jingfang Hu; Limin Chen; Ye Hong; Wenjin Chen (Journal of Water Process Engineering, 2026)

To be integrated or not? Understanding continuance behavioral intention towards integrated ride-hailing services: Empirical evidence from Nanjing, China - Ke Lu; Jingfang Hu; Tingyu Shang; Yuan Xu (Sustainable Cities and Society, 2026)

Effects of stir-frying frequency on meat quality via multimodal infrared & accelerometer platform - Yibing Yuan; Liangyu Xue; Xiaojia Hu; Guowei Gao; Wenzheng Zhu; Yangjun Wang; Jingfang Hu; Huixin Tian; Chunhui Zhang; Wensong Wei (International Journal of Gastronomy and Food Science, 2025)

Raw meat 3D laser scanning imaging: Optimized by adaptive contour unit - Lingping Bu; Huixin Tian; Zhen Qiao; Xiaojia Hu; Guowei Gao; Bo Qi; Zhize Wang; Jingfang Hu; Chunhui Zhang; Dequan Zhang; Wensong Wei (Food and Bioproducts Processing, 2025)

Double template synthesis of N/S co-doped shrimp shell derived biochar for efficient sulfadiazine degradation: The role of non-radical pathway - Yulai He; Jiaqi Wang; Lele Lei; Yushi Ai; Hongmei He; Jin Huang; Limin Chen; Jingfang Hu; Wenjin Chen (Journal of Environmental Chemical Engineering, 2024)

Genome-wide association mapping combined with gene-based haplotype analysis identify a novel gene for shoot length in rice (Oryza sativa L.) - Tifeng Yang; Jingfang Dong; Junliang Zhao; Longting Zhang; Lian Zhou; Wu Yang; Yamei Ma; Jian Wang; Hua Fu; Jiansong Chen; Wenhui Li; Haifei Hu; et al. (Theoretical and Applied Genetics, 2023)
Key message Genome-wide association mapping revealed a novel QTL for shoot length across multiple environments. Its causal gene, LOC_Os01g68500 , was identified firstly through gene-based haplotype analysis, gene expression and knockout transgenic verification. Abstract Strong seedling vigor is an important breeding target for rice varieties used in direct seeding. Shoot length (SL) is one of the important traits associated with seedling vigor characterized by rapid growth of seedling, which enhance seedling emergence. Therefore, mining genes for SL and conducting molecular breeding help to develop varieties for direct seeding. However, few QTLs for SL have been fine mapped or cloned so far. In this study, a genome-wide association study of SL was performed in a diverse rice collection consisting of 391 accessions in two years, using phenotypes generated by different cultivation methods according to the production practice, and a total of twenty-four QTLs for SL were identified. Among them, the novel QTL qSL-1f on chromosome 1 could be stably detected across all three cultivation methods in the whole population and indica subpopulation. Through gene-based haplotype analysis of the annotated genes within the putative region of qSL-1f , and validated by gene expression and knockout transgenic experiments, LOC_Os01g68500 (i.e., Os01g0913100 in RAP-DB) was identified as the causal gene for SL, which has a single-base variation (C-to-A transversion) in its CDS region, resulting in the significant difference in SL of rice. LOC_Os01g68500 encodes a DUF538 (Domain of unknown function) containing protein, and the function of DUF538 protein gene on rice seedling growth is firstly reported in this study. These results provide a new clue for exploring the molecular mechanism regulating SL, and promising gene source for the molecular breeding in rice.

Vegetation restoration enhances soil erosion resistance through decreasing the net repulsive force between soil particles - Rentian Ma; Feinan Hu; Chenyang Xu; Jingfang Liu; Zhenghong Yu; Gang Liu; Shiwei Zhao; Fenli Zheng (CATENA, 2023)

Evaluating the effect of soil internal forces on the stability of natural soil aggregates during vegetation restoration - Rentian Ma; Feinan Hu; Jingfang Liu; Shiwei Zhao (Journal of Soils and Sediments, 2021)

OsNDUFA9 encoding a mitochondrial complex I subunit is essential for embryo development and starch synthesis in rice - Tingting Hu; Yunlu Tian; Jianping Zhu; Yunlong Wang; Ruonan Jing; Jie Lei; Yinglun Sun; Yanfang Yu; Jingfang Li; Xiaoli Chen; Xiaopin Zhu; Yuanyuan Hao; et al. (Plant Cell Reports, 2018)

Construction and characterization of the interdomain chimeras using Cry11Aa and Cry11Ba from Bacillus thuringiensis and identification of a possible novel toxic chimera - Yunjun Sun; Qiang Zhao; Dasheng Zheng; Xuezhi Ding; Jingfang Wang; Quanfang Hu; Zhiming Yuan; Hyun-Woo Park; Liqiu Xia (Biotechnology Letters, 2014)